Representasi Nilai Optimisme dalam MV PLAVE “The 6th Summer” - Irfiyani, Khoirunnisa; Yoedtadi, Moehammad Gafar (Koneksi, 2025)
With the evolution of the digital era, the role of avatars has become increasingly important, and virtual idols have emerged as an important phenomenon in popular culture. Currently, PLAVE has become a popular virtual idol and streamer in South Korea and internationally. In this case, virtual idols often insert various symbols and signs including in MVs. PLAVE's MV "The 6th Summer" conveys the message that the desire for something more than just a dream, appreciates every moment that has been passed and the hope to do something meaningful amidst life's challenges. This study aims to determine the representation of the value of optimism in PLAVE's MV "The 6th Summer". The research method uses Roland Barthes' semiotic analysis with the meaning of denotation, connotation, and myth. The results of this study indicate that the value of optimism through visual elements in the scene and lyrics about the importance of hard work and optimism in facing life's challenges. Representation of the value of optimism that can be obtained through hard work, hope for the future, togetherness, and happiness. So that it is important to foster positive thinking in each individual in order to face obstacles in life. Dengan evolusi era digital, peran avatar menjadi semakin penting, dan virtual idol muncul sebagai fenomena penting dalam budaya populer. Saat ini, PLAVE telah menjadi idol dan streamer virtual populer di Korea Selatan dan internasional. Dalam hal ini, virtual idol sering kali menyisipkan berbagai simbol dan tanda termasuk dalam MV. MV PLAVE “The 6th Summer” ini menyampaikan pesan bahwa keinginan untuk sesuatu yang lebih dari sekedar mimpi, menghargai setiap momen-momen yang telah dilewati dan harapan untuk melakukan sesuatu yang bermakna di tengah tantangan hidup. Penelitian ini bertujuan untuk mengetahui representasi nilai optimisme dalam MV PLAVE “The 6th Summer”. Metode penelitian menggunakan analisis semiotika Roland Barthes dengan pemaknaan denotasi, konotasi, dan mitos. Hasil dari penelitian ini menunjukkan bahwa nilai optimisme melalui elemen visual pada adegan dan lirik tentang pentingnya kerja keras dan optimisme dalam menghadapi tantangan hidup. Representasi nilai optimisme yang dapat diperoleh melalui kerja keras, harapan akan masa depan, kebersamaan, dan  kebahagiaan. Sehingga pentingnya menumbuhkan pemikiran positif dalam diri setiap individu agar dapat menghadapi rintangan dalam hidup.